Modified inderbitzen equipment for simulation of water erosion in undeformed soil samples - Thoma, Andréa Cristina; Tassinari, Diego; Prat, Bernat Vinolas; Dos Santos, Lauana Lopes; Silva, Bárbara Pereira Christofaro [UNESP]; Silva, Alexandre Christofaro (Zeppelini Editorial e Comunicacao, 2023)
Several devices have been developed to assess soil losses by water erosion. However, they rarely assess the combined effects of raindrop impact and surface runoff together with vegetation cover on varying slopes. This study aimed to design and validate an equipment, on laboratory scale, to evaluate the effect of water erosion on undisturbed soil samples with and without plant cover, as well as to assess the kinetic energy of simulated rain and the resultant shear stress at varying runoff intensities. The equipment is composed of a rainfall simulator, an adjustable stand for different slopes and falling heights, and a runoff ramp for testing undisturbed soil samples measuring 15 x 20 x 40 cm (height, width, and length). In this study, the equipment simulated and evaluated the effect of precipitation and runoff on soil losses, allowing to obtain different values of the kinetic energy of precipitation and runoff. For a flow rate of 12 L min-1 and slope of 35%, the shear stress could reach up to 8 Pa. Furthermore, the equipment showed the effect of vegetation cover and slope on soil losses in different granulometric fractions (< 0.106 mm, 0.106 to 0.25 mm, 0.25 to 0.5 mm, 0.5 to 1.0 mm, 1.0 to 2.0 mm, and > 2.0 mm), revealing the potential of its use in several erosion studies on a laboratory scale.
Equipamento inderbitzen modificado para simulação da erosão hídrica em amostras de solo indeformado
Keywords: erosometer; Lithic Quartzipsamment; rainfall simulator; surface runoff